Problems of Milk Quota Management in Acco¬un¬ting System their Effect on Property Status of Enterprises - Kiss Árpád (ACTA AGRONOMICA ÓVÁRIENSIS, 2009)
According to both international and Hungarian accounting standards milk quota shall be capitalised among the assets of the enterprises. It is necessary for the implementation of the activity; its value can be defined based on market processes and regulations of the authorities. Due to the possibility of trading quotas on the market it would be the only solution to avoid the recognition of requested and purchased quotas on different values in the accounting system. Considering the total amount of quotas a HUF 40 billion increase of assets could be reached by the enterprises in milk production, if quotas were recognized among the intangible assets. Based on the results of a questionnaire survey the majority of enterprises did not perform the valuation tasks, therefore the total asset value is lower than the realistic value by HUF 50 million (by 7.2% of the total asset value). The study introduces the possible methods of the calculation of historical cost and depreciation.